Diagnosis Miokarditis yang Tertunda Setelah Trauma Tumpul Abdomen: Sebuah Laporan Kasus Langka: Laporan Kasus - Kaiba, Astrid Carolinn Valleriana; Kuntadi, Putu Aditya Darmawan; Athoillah, Nabil (Cermin Dunia Kedokteran, 2026)
Introduction: Myocarditis is an inflammation of the myocardium that can lead to impaired heart function and sudden death. Most cases are caused by viral infections and are very rarely reported as a post-traumatic complication. Case: A 54-year-old male developed abdominal pain and vomiting after blunt abdominal trauma. The patient was initially diagnosed with colonic rupture and underwent exploratory laparotomy. Despite initial improvement, the patient experienced hemodynamic deterioration. Electrocardiography, cardiac biomarkers,and echocardiography evaluation revealed myocarditis with decreased ejection fraction. Despite supportive and pharmacological therapy, the patient fell into cardiogenic shock and passed away. Discussion: This case demonstrates that the diagnosis of myocarditis can besignificantly delayed in patients with atypical presentations and no obvious cardiac symptoms. Abdominal trauma accompanied by systemic infection, such as colonic rupture, may potentially cause secondary myocardial inflammation. Clinicians need to consider the possibility of myocarditis in patients with postoperative hemodynamic instability, even without a history of cardiac disease. Conclusion: This report highlights the urgency of improving diagnostic awareness of myocarditis and access to support facilities.